2016
DOI: 10.3389/fphar.2016.00048
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol-Rich Extract of Syzygium cumini Leaf Dually Improves Peripheral Insulin Sensitivity and Pancreatic Islet Function in Monosodium L-Glutamate-Induced Obese Rats

Abstract: Syzygium cumini (L.) Skeels (Myrtaceae) has been traditionally used to treat a number of illnesses. Ethnopharmacological studies have particularly addressed antidiabetic and metabolic-related effects of extracts prepared from its different parts, especially seed, and pulp-fruit, however. there is a lack of studies on phytochemical profile and biological properties of its leaf. As there is considerable interest in bioactive compounds to treat metabolic syndrome and its clustered risk factors, we sought to chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 78 publications
5
35
0
Order By: Relevance
“…Third sample collected from Bogor Botanical Garden, located in west Java, altitude above sea level ± 290 m with average rainfall per year 3500 mm. Samples were extracted using 70% ethanol at room temperature to obtain a high content of phenolic compounds 16 and avoid any degradation of active compounds during extraction which can be caused by heat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third sample collected from Bogor Botanical Garden, located in west Java, altitude above sea level ± 290 m with average rainfall per year 3500 mm. Samples were extracted using 70% ethanol at room temperature to obtain a high content of phenolic compounds 16 and avoid any degradation of active compounds during extraction which can be caused by heat.…”
Section: Discussionmentioning
confidence: 99%
“…Chagas et al 15 summarized the activity of S. cumini against cardiometabolic diseases such as antihyperglycemic, antihyperlipidemic, cardioprotective, anti-inflammatory and antioxidant activities based on experimental studies. Hydroethanolic extract of S. cumini leaves reported having a high total of polyphenol content, antioxidant activity, improves insulin sensitivity 16 and antihypertensive effect 17 .…”
Section: Introductionmentioning
confidence: 99%
“…have been found to affect blood lipids positively and it has been found that the polyphenols present in them exert their effect by inhibiting critical steps in the intestinal absorption of dietary fat, cholesterol and other lipids, decreasing oxidation of LDL-C and arresting vascular inflammation. 30,31 In addition to this, alcoholic beverages like red wine have been found to correct the dyslipidemia in diabetic animals and humans. However, the effect was not observed in case of white wine and gin as they are devoid of such bio-active compounds.…”
Section: Discussionmentioning
confidence: 99%
“…SC leaf is reported to be rich in flavonoids such as myricetin, myricitrin, quercetin, kaempferol, ellagic acid, ferulic acid and gallic acid (Ruan et al, 2008;Ayyanar & Subash-Babu, 2012). Ellagitannins and gallotannins also were identified from the SC leaf ethanolic extract (Sanches et al, 2016).…”
Section: September 2018mentioning
confidence: 99%